PERTUMBUHAN DAN PRODUKSI SAYURAN MODEL MINI WALL GARDEN DI DKI JAKARTA - Yudi Sastro; Chery Soraya Ammatillah; Indarti Puji Lestari (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACT The Growth and Production of Vegetables within Mini Wall Garden in DKI Jakarta Province. Saving land cultivation technology is one of the alternative solutions to address the limited availability of land for plant cultivation in urban areas.  This study aimed to compare of two models of vegetables mini-wall garden at households scale in urban areas. The study was conducted in three farmer groups in South of Jakarta, i.e. Puspa Asri, Melati, dan Kenanga. Each farmer groups were involved five cooperators as replications. The models tested were pocket models and PVC pipe models. Growth and yield of kangkong, spinach, green mustard, and lettuce were used as observation variables. The plant response data were analyzed using t-test at 0.5%. The feasibility of technology was analyzed using R/C ratio, meanwhile the average score analysis used for variable of user’s perception. Based on of the plant response and economic benefits gained, the PVC pipe model is better than the pocket model. Based on user's perception both models has good perception categories. The assessment results indicate that the technology of the mini wall garden PVC pipe model more efficient than pocket model, so in the future to develop vegetables in mini wall garden models suggested using PVC pipe models. Keywords: Wall garden, innovation, vegetableABSTRAKTeknologi budidaya hemat lahan merupakan salah satu alternatif pemecahan masalah terbatasnya ketersediaan lahan untuk budidaya tanaman di perkotaan. Pengkajian bertujuan untuk membandingkan dua model mini wall garden sayuran skala pekarangan di perkotaan. Kegiatan pengkajian dilakukan di tiga kelompok tani di wilayah Jakarta Selatan, yaitu Kelompok Tani Puspa Asri, Melati, dan Kenanga tahun 2013. Setiap kelompok tani melibatkan lima orang kooperator, masing-masing sebagai ulangan. Model yang diujikan adalah model kantong dan model paralon PVC. Pertumbuhan dan hasil kangkung, bayam, caisim, dan selada sebagai peubah pengamatan. Data respon tanaman di analisis menggunakan uji-t pada taraf uji 0,5%. Kelayakan teknologi dihitung menggunakan R/C, sedangkan persepsi petani atau pengguna dihitung berdasarkan skor data rataan. Berdasarkan respon tanaman dan keuntungan ekonomi, model pipa PVC nyata lebih baik dibandingkan model kantong. Berdasarkan persepsi pengguna, kedua model mini wall garden tersebut memiliki kategori baik. Hasil pengkajian mengindikasikan bahwa teknologi mini wall garden  model paralon lebih efisien dibandingkan model kantong, sehingga untuk mengembangan sayuran model mini wall garden ke depan disarankan menggunakan model paralon. Kata kunci: Wall garden, inovasi, sayuran